The Mundaneness of Oppression: Translation, Silence, and Reception in Kim Ji-young, Born 1982. - Thakur, Ashita (Intersections: Gender & Sexuality in Asia & the Pacific, 2026)
With the enduring difficulty in translating narratives of suffering, it is rare for a novel focusing on gendered trauma to achieve the same level of success as Nam Joo Cho’s Kim Ji-young, Born 1982, the second book from South Korea, which became a million-seller in 2016. The novel employs a sparse narrative style, almost clinical in its delivery and often perceived as ’bland’ by many non-Korean readers, which resists western understandings of fiction. This article examines how the novel’s English translation negotiates structural irony, narrative ambiguity, and cultural idiom in its representation of gendered trauma. It questions how silence is constructed as a narrative strategy, and how it is mediated and interpreted in translation. Methodologically, this article combines close textual analysis with a reception study and content analysis of a selected sample of Goodreads’ reviews to evaluate readers’ responses to the novel’s sparse, bureaucratic narrative style and documentary footnotes. Drawing on feminist translation theory and reception theory, this article demonstrates how silence serves as a deliberate strategy to counter epistemological violence in the Korean text. While the translation mostly preserves structural irony, reader reception reveals the complex terrain of translational ethics. The article ultimately presents translation as a site where cultural legibility, feminist politics, and reader expectation intersect, unveiling its possibilities and limitations.